AVERTING THE SUBPRIME CRISIS: AN ISLAMIC PERSPECTIVE - Iawidat, Nidal (2008)
This dissertation uses the Zakah funds, a new innovation in the Muslim world to collect religious alms "The Zakah", to overcome the market failure inherent in the credit provision transitions. As such, it introduces a socio-economic framework for integrating Zakah funds with Rotating Savings and Credit Associations (ROSCAs) to finance those borrowers classified as risky by formal financial institutions. It comes in light of recent voices to tap upon unutilized indigenous philanthropy in financing those who are marginalized by the mainstream financial sector (White, 2006; Bremer, 2004; UN-Habitat, 2005) and in light of the recent subprime crisis which proved to be exclusionary to those borrowers.